Structural topology optimization of layout and raster angle for additive manufacturing technology with the shadow density filter. (November 2021) - Yoon, Gil Ho
Highlights: A new shadow density filter to consider the overhang constraint. Allowing the self-supporting structures in topology optimization. Proving experimentally the importance of the raster angles. Concurrently optimizing topology as well as raster angles. Overcoming the limitation of the isotropic material. Abstract: The present research contributes in the structural topology optimization with the manufacturing limitation called the overhang constraint and the optimization of the anisotropic material properties. For the optimization with self-supporting structure, the overhang-free shadow filter method is developed. To consider the anisotropic material property, the raster angles of each layer (the printing direction used to print structures) are optimized simultaneously with topology. By adding the raster angles as the design variables, it is possible to find out optimal layouts as well as optimal raster angles considering the anisotropicity. Several numerical examples of compliance minimization problem are solved to demonstrate the validity and effectiveness of the present density filter and to show the importance of the raster angle.